ELT Student Teacher Identity Construction: Exploring Teacher Roles and Domains of Expertise - Aktekin, Nafiye Cigdem; Celebi, Hatice (Universitas Negeri Makassar, 2020)
In this study, we direct our focus to identity construction in an English language teaching (ELT) teacher education program. We explore the teacher roles in which student teachers are struggling to position themselves comfortably and the teacher expertise domains (subject matter, didactics, and pedagogy) that they are dedicating themselves to improving. To address our research focus, we have collected reflections and survey responses from 18 student teachers in an ELT education department. Our findings indicate that ELT student teachers find it difficult to position themselves as experts in and about the English language and that they feel a need to be equipped with expertise first and foremost in the subject matter, and then in didactics, followed by pedagogy. These results imply that in ELT teacher education, certain language ideologies are still prevalent and need to be dealt with by teacher educators for transformative outcomes in education.